HEALTH TECHNOLOGIES: COLLECTIVE IMPACTS - Carolina Salustino dos Santos, Maria; Emília Araújo de Oliveira, Ana; Carvalho Lima, Raquel; Vitória Gomes Lins Paz, Iracema; Figueiredo da Silva, Yasmin; Marília Lima Guida, Vânia; Martins Gonçalves, Albertina; Evelly da Silva Olanda, Debora; Fernandes Filgueiras, Mateus; Flávia Freitas de Miranda Coêlho, Ana; de Araújo Evangelista, Wanessa; Barros de Valmoré Fernandes, Marcelo; et al. (Health and Society, 2022)
The use of health technologies provides better health management, anchored in equity, communication and governance in health. Technologies are conceptualized as a tool, which helps from planning to the execution of activities, and can be applied in health or in another area of knowledge. The objective is: to analyze scientific productions related to health technologies in a collective perspective. This study takes the form of an integrative literature review, built through the following steps: definition of the research question, selection of descriptors, choice of database, search and organization of articles and presentation of results. The chosen databases were: Latin American and Caribbean Literature in Health Sciences - LILACS, Medical Literature Analysis and Retrievel System Online - MEDLINE, Google Scholar and Scientific Electronic Library Online - SciELO, from July to August, year of 2022. Eight studies on the topic were gathered and organized in a table. The results obtained from the research carried out through scientific articles related to health technology and the collective impacts, several concepts were analyzed about the word technology, the main ones being: “light technology”, “light-hard technology” and “hard technology” . It was observed that there is a generalization of these mentioned terms, which are related to the reception along with the dialogue, the information and the production of procedures, respectively.